Ellison Orr letter to Oscar Allert regarding Peregrine Falcon sightings, March 10, 1934 - Orr, Ellisonet al (1934)
Letter from Ellison Orr to Oscar Allert dated March 10, 1934. Orr tells Allert that he has frequently seen Peregrine Falcons and that Philip DuMont is incorrect in claiming that the Peregrine Falcon is rare in Iowa and has not nested in Iowa since 1898. This letter was summarized in Allert's article "Notes on Certain Raptores in Allamakee, Clayton and Dubuque Counties, Iowa," published in Iowa Bird Life, vol. 9, no. 3. Epson - sheet feed/flatbed